Analysis of Users’ Perception of Home Care Provided by the Family Health Strategy Team: A Quali–Quantitative Approach - Marconato, José Victor; Genaro, Luís Eduardo [UNESP]; Valsecki Junior, Aylton [UNESP]; Lopez Rosell, Fernanda [UNESP] (MDPI, 2024)
Background/Objective: Home care involves actions and services aimed at promoting health. Despite being an important strategy for humanized care, strengthening bonds, and improving access, there is a lack of scientific evidence regarding users’ perceptions of home care. The objective of this study was to analyze the perception of users regarding the home care provided by the Family Health Strategy team. Methodology: A descriptive, quali–quantitative approach was used, with a sample of 60 patients who required home care. Interviews were conducted using a semi-structured guide, and the analysis applied the Collective Subject Discourse. Results: Most participants were female (60%) and aged between 71 and 85 years (45%). The duration of home care varied, with 41.6% receiving care for 13 to 24 months. The majority of participants (61.6%) received home care weekly, while 33.4% were visited every 15 days, and 5% monthly. The most present professionals were community health agents (45%), followed by nursing assistants (18.3%), nurses (15%), and doctors (15%). Dentists and physiotherapists made fewer visits (3.3%). Regarding the care received, 36.6% valued the continuity of treatment, 31.6% were satisfied with the quality, and 25% highlighted the humanization of care. Only 6.6% desired more frequent visits. Conclusions: The analysis of perceptions revealed that participants valued the continuity of treatment and the quality of care received. Home visits were predominantly carried out by community health agents.
Keywords: discourse of the collective subject; home care services; qualitative research